Pneumatology and the constitution of socio-spiritual communities - Kirsch, Thomas G. (Kolner Zeitschrift fur Soziologie und Sozialpsychologie, 2013)
This chapter brings together approaches from social anthropology and sociology in order to explore with a view to ethnographic research data from southern Africa (Zambia) the relationship between the life-world effects of Pentecostal theologies relating to the Holy Spirit (pneuma) on the one hand, and Pentecostal modalities of constituting translocal communities on the other. This focus allows to question conventional understandings of religious sociality as well as to carve out three different ways of establishing what I call 'socio-spiritual communities': In the mode of the 'logistics of the spirit', a given Pentecostal community expands in the socio-spatial logic of a network, meaning that the spatial movements of the Holy Spirit run parallel to the spatial movements of its human vessels; in the mode of the Holy Spirit's 'selfmultiplication', Pentecostal sociality takes the form of a scattering in which autonomous enclaves of spiritualization are connected to each other; finally, 'spiritual scaling' represents a mode of spiritual omnipresence in socio-religious space that is affected by changes in the Holy Spirit's scalar morphology. © 2013 Springer Fachmedien Wiesbaden.
Free
Keywords: Anthropology; Network; Pentecostalism